The efficacy of a supervised exercise training programme on readmission rates in patients with myocardial ischemia: results from a randomised controlled trial. (1st March 2017) - Santaularia, Núria; Caminal, Josefina; Arnau, Anna; Perramon, Montserrat; Montesinos, Jesus; Abenoza Guardiola, Montserrat; Jaarsma, Tiny
Abstract: Background: The results of research into the outcomes of physical rehabilitation and its relationship with post-myocardial ischaemia survival and readmissions are inconclusive. Our primary aim was to evaluate the efficacy of a supervised exercise training programme in terms of decreasing hospital cardiac readmission in patients with myocardial ischaemia. Methods: We conducted a randomised controlled trial including patients with myocardial ischaemia. Eligible patients were assigned to a control group receiving standard care or to an intervention group that took part in a supervised exercise training programme. The follow-up period was 12 months after hospital discharge. Results: Of 478 patients assessed for eligibility, 86 were randomised to the control group ( n = 44) or the intervention group ( n = 42). Cardiac readmission rates were 14% versus 5% ( p = 0.268) in the control and intervention groups, respectively, and all-cause readmission rates were 23% versus 15% ( p = 0.34). There were no deaths in either group. More control patients were treated in the emergency services (50% vs. 24%; p = 0.015). In terms of health-related quality of life, patients in the intervention group presented with significant increases in functional capacity and mobility. More intervention patients returned to work (77.3% vs. 36.0%; p = 0.005). Conclusions: The supervised physical exercise programme was effective at reducing the number of emergency room visits and at increasing the percentage of patients who returned to work. It also improved patients' exercise capacity and increased their health-related quality of life. Although the results were promising, the programme was not associated with a significant reduction in cardiac and all-cause readmission rates.